European Commentaries on Private International Law. - Bogdan, Michael, 1946-; Calvo Caravaca, Alfonso-Luis; Carrascosa González, Javier; Fentiman, Richard; Ferrari, Franco, 1965-; Franzina, Pietro; Heiss, Helmut; Hellner, Michael; Honorati, Costanza; Liukkunen, Ulla; Machnikowski, Piotr; Magnus, Ulrich, 1944-; et al. (Magnus/Mankowski, European Commentaries on Private International Law ;, 2019)
Today car crashes, holiday accidents, damage through defective products and other tort situations, that occur in Europe, not infrequently involve a foreign element. It is then always of crucial importance which law applies. For the first time the EU has unified the private international law rules for extra-contractual relations in the Rome II Regulation. The instrument is in force in all EU Member States (with the only exception of Denmark) since 2009. Meanwhile the European Court of Justice and national courts have rendered a considerable number of decisions concerning central provisions of the Regulation. The time is therefore ripe for a truly pan-European Commentary on the Rome II Regulation which can give guidance in its interpretation. The Commentary takes full account of the European nature of this instrument. This is also reflected by the team of contributors that originates from all over Europe assembling first experts in their countries. As the other works of the European Commentaries on Private International Law series this book provides a thorough article-by-article analysis which intensely uses the case law and doctrine and suggests clear and practical solutions for disputed issues. The editors are Ulrich Magnus and Peter Mankowski who have already edited pan-European Commentaries on the Brussel I Regulation, the Brussels Ibis Regulation, the Rome I Regulation and the Brussels IIbis Regulation.